2017
DOI: 10.1002/tesj.362
|View full text |Cite
|
Sign up to set email alerts
|

The use of video feedback in teaching process‐approach EFL writing

Abstract: This experimental study investigated the use of video feedback as an alternative to feedback with correction codes at an institution where the latter was commonly used for teaching process-approach English as a foreign language (EFL) writing. Over a 5-week period, the control and the experimental groups were provided with feedback based on comments and correction codes and video feedback, respectively, and the extent of feedback incorporation was analyzed through descriptive and inferential statistics. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 22 publications
3
21
0
Order By: Relevance
“…The quantitative and qualitative data indicated that the lecturers provided comprehensive feedback on all aspects of writing, including language use, mechanics and referencing style, content, and organisation and rhetoric. This finding accords with many previous studies on screencast feedback in L2 writing (e.g., Ali, 2016;Bakla, 2020;Ducate & Arnold, 2012;Özkul & Ortactepe, 2017;Tseng & Yeh, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The quantitative and qualitative data indicated that the lecturers provided comprehensive feedback on all aspects of writing, including language use, mechanics and referencing style, content, and organisation and rhetoric. This finding accords with many previous studies on screencast feedback in L2 writing (e.g., Ali, 2016;Bakla, 2020;Ducate & Arnold, 2012;Özkul & Ortactepe, 2017;Tseng & Yeh, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…The results have shown that students showed positive perception of screencast feedback (e.g., Cunningham, 2019). Similarly, studies on student"s perception of screencast feedback in L2 writing (Alvira, 2016;Ghosn-Chelala & Al-Chibani, 2018;Orlando, 2016;Özkul & Ortactepe, 2017;Tseng & Yeh, 2019) have reported students" positive perceptions of teacher screencast feedback.…”
Section: Literature Reviewmentioning
confidence: 66%
See 2 more Smart Citations
“…To manage such constrains, teachers need to employ some professional adjustment (Ferris, Brown, Liu, Eugenia, and Stine, 2011) by dealing with three crucial contextual variables that are learners, situation, and instructional methodology (Hartshorn, McCollum, and Wolfersberger, 2010). Several attempts have also been empirically tested for example the use of video which is multimodal for conferencing thus the information delivered to the students could be richer (Ozkul and Ortactepe, 2017), the addition of affective comments to complement the written corrective feedback (Tang and Liu, 2018), the use of models (Mayo and Labandibar, 2017), and the application of supplementary rubrics (Ene and Kosobucki, 2016). Besides, reciprocal caring and dialogue interactions between teachers and students during the writing process could improve trust (Lee and Schallert, 2008) which then facilitate the linguistic revisions of the student writing (Merkel, 2018).…”
Section: Teachers' Perceptions and Practicesmentioning
confidence: 99%